2020
DOI: 10.5194/acp-20-7411-2020
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and geochemistry of Asian dust: dependence on migration path, fractionation, and reactions with polluted air

Abstract: Abstract. Mineralogical and geochemical data are essential for estimating the effects of long-range transport of Asian dust on the atmosphere, biosphere, cryosphere, and pedosphere. However, consistent long-term data sets of dust samples are rare. This study analyzed 25 samples collected during 14 Asian dust events occurring between 2005 and 2018 on the Korean Peninsula and compared them to 34 soil samples (<20 µm) obtained from the Mongolian Gobi Desert, which is a major source of Asian dust. The mineralog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 67 publications
3
27
0
Order By: Relevance
“…Back trajectories calculated with the HYSPLIT model 35 confirm that most of the days the air masses were coming from the north and likely include dust from the Gobi desert, mixed with regional and local particles, local soil, and dust. In a mineralogy study by Jeong 36 high amounts of S were shown in dust events in the area, in addition to the mineral dust elements. The low contribution of V and BC indicates that heavy fuel oil combustion is not a major contributor to factor 1.…”
Section: Resultsmentioning
confidence: 99%
“…Back trajectories calculated with the HYSPLIT model 35 confirm that most of the days the air masses were coming from the north and likely include dust from the Gobi desert, mixed with regional and local particles, local soil, and dust. In a mineralogy study by Jeong 36 high amounts of S were shown in dust events in the area, in addition to the mineral dust elements. The low contribution of V and BC indicates that heavy fuel oil combustion is not a major contributor to factor 1.…”
Section: Resultsmentioning
confidence: 99%
“…The data coverage of the mineralogical database for East Asia is not satisfactory as much of the information for this region is compiled in Chinese language publications . Indeed, the Fe content is relatively enriched in Asian dust (5.27 ± 0.25%) compared to the global average . Thus, the regionally averaged Fe content (35–50°N, 70–120°E) for each Fe species in clay-sized soils was scaled to that in the clay-sized fraction of Chinese desert sediments .…”
Section: Methodsmentioning
confidence: 99%
“…50 Indeed, the Fe content is relatively enriched in Asian dust (5.27 ± 0.25%) compared to the global average. 53 Thus, the regionally averaged Fe content (35−50°N, 70−120°E) for each Fe species in clay-sized soils was scaled to that in the clay-sized fraction of Chinese desert sediments. 54 The scaling factors of the Fe content, which were used to estimate lithogenic emissions of Fe from clay-sized soils in the simulations, are presented in the Supporting Information (Table S4).…”
Section: Atmospheric Chemical Transportmentioning
confidence: 99%
“…Iron-bearing particles derived from mineral dust and anthropogenic Fe have different chemical compositions and mineralogy. Mineral dust is mainly composed of crystalline aluminosilicates (Jeong and Achterberg, 2014;Jeong, 2020). Fly ash emitted from anthropogenic high-temperature combustion processes can be categorized into two groups: non-magnetic and magnetic particles.…”
Section: Introductionmentioning
confidence: 99%